2012
DOI: 10.1016/j.foodchem.2012.01.041
|View full text |Cite
|
Sign up to set email alerts
|

Chemopreventive potential of the tannase-mediated biotransformation of green tea

Abstract: Green tea (Camellia sinensis) is one of the most widely consumed beverages in the world. The cancer chemopreventive qualities of green tea have been well documented. Epigallocatechin gallate (EGCG) is often described as the most potently chemopreventive green tea catechin; however, the low bioavailability of EGCG is a limiting factor for its biological effect. Thus, the aim of this work was to test the chemopreventive potential of green tea extract and EGCG after tannase-mediated hydrolysis. The results showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 43 publications
2
15
0
1
Order By: Relevance
“…The antioxidant activities of the green tea extract increased by 39% after enzymatic treatment. Gallic acid can be formed by the degalloylation of the EGCG present in the green tea extract (Macedo et al ., ). We demonstrated that biotransformed green tea extract had a higher gallic acid content compared to the native green tea extract (Table ).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…The antioxidant activities of the green tea extract increased by 39% after enzymatic treatment. Gallic acid can be formed by the degalloylation of the EGCG present in the green tea extract (Macedo et al ., ). We demonstrated that biotransformed green tea extract had a higher gallic acid content compared to the native green tea extract (Table ).…”
Section: Resultsmentioning
confidence: 97%
“…The lyophilised tea extract (1.0 mg) was dissolved in 1.0 mL of citrate buffer (pH 4.7, 50 m m ) and incubated with 1.0 mg of tannase at 30 °C for 30 min. The reaction tubes were placed in an ice bath for 15 min to constrain the progress of enzymatic reaction (Macedo et al ., , ).…”
Section: Methodsmentioning
confidence: 99%
“…For example, the antioxidant capacity of soybean flour was enhanced by the enzymatic hydrolysis of phenolic glucoside in solid-state fungi fermentation [19]. In particular, tannase (EC 3.1.1.20; tannin acyl hydrolase) shows good ability in the bioconversion of green tea extract (GTE), resulting in gallic acid (GA) and degalloylated catechins [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Increasing the content of GA through the conversion of GTE by tannase has been shown to improve the radical scavenging activities of GTE [22]. Moreover, conversion of (-)-epigallocatechin gallate (EGCG) by tannase attenuated its toxicity without affecting the antiproliferative effects [21]. Another study demonstrated that tannase-treated catechins influenced the expression of genes involved in the sodium-glucose transport proteins [23].…”
Section: Introductionmentioning
confidence: 99%
“…Among these, catechins and polysaccharides, which have been used in the food industry and in medicine, have received much attention in recent years due to their biological activities . Macedo et al recently reported the chemopreventive potential of tannase‐mediated biotransformation in green tea extract. Interestingly, a recent study showed that fermentation using microbes also could be used to increase antioxidant activities of polyphenol solution …”
Section: Resultsmentioning
confidence: 99%